Um caminho, múltiplas escolhas: Carlos de Souza Moraes e sua atuação político-intelectual no Rio Grande do Sul (1930-1950) - Santos, Rodrigo Luis dos (Universidade do Vale do Rio dos Sinos, 2021)
Carlos de Souza Moraes (Montenegro / RS, 1908 - São Leopoldo / RS, 2003) began his professional career in law, which he exercised for a large part of his life, but he worked mainly in the fields of politics and intellectuality. In São Leopoldo, he served as secretary of the City Hall (1937-1944), director of Public Instruction (1939-1944), director of the official newspaper Correio de São Leopoldo (1938-1944), mayor (1944-1945 / 1946- 1947) and councilman (1948-1951). Still in the 1930s, he began his intellectual trajectory, joining the Rio-grandense Academy of Letters in 1938, later joining the Historical and Geographic Institute of Rio Grande do Sul and the Historical Institute of São Leopoldo, of which he was one of the founders, in 1975. Our objective is to critically analyze this trajectory, in the light of current historiography, especially that which refers to biographical studies, using the methodological instruments of Microhistory. At the same time, we seek to understand the trajectory and performance of Carlos de Souza Moraes within a perspective that also expands the range of analysis, also aiming to understand the socio-political and cultural construction in which this historical agent participates at the regional and state level, whether by through the relationships he established, the positions he held, the institutions he participated in and the intellectual works he produced.
Keywords: Carlos de Souza Moraes; Trajetória; Política; Intelectualidade; Trajectory; Policy; Intellectuality; ACCNPQ::Ciências Humanas::História